1989
DOI: 10.1152/jappl.1989.66.4.1838
|View full text |Cite
|
Sign up to set email alerts
|

Sulfidopeptide leukotrienes mediate acrolein-induced bronchial hyperresponsiveness

Abstract: The sulfidopeptide leukotrienes are bronchoconstrictive lipid mediators thought to have an important role in the pathophysiology of asthma. The objective of this study was to determine if treatment with a leukotriene receptor antagonist and 5-lipoxygenase inhibitors could diminish acrolein-induced bronchial hyperresponsiveness and to determine whether leukotriene (LT) C4 generation is augmented by acrolein exposure. Guinea pigs (groups of 6-7) were exposed to 1.3 ppm acrolein for 2 h and bronchial responsivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Acrolein (2.0 mg/m 3 ×2 h) also increased bronchial hyperreactivity that was evident within 1 h, maximal at 2–4 h, and persisted up to 24 h after exposure 98. This exposure was accompanied by increases in bronchoconstrictive lipid mediators (thromboxane B2, prostaglandin F2 α, and leukotrienes) immediately after exposure, and delayed influx of neutrophils (24 h) 98, 99. These temporal relationships suggest that neutrophil infiltration may be a sufficient but not a necessary condition for the onset of bronchial hyperreactivity and that injury to cells normally present in the lung, e.g.…”
Section: Responsementioning
confidence: 95%
“…Acrolein (2.0 mg/m 3 ×2 h) also increased bronchial hyperreactivity that was evident within 1 h, maximal at 2–4 h, and persisted up to 24 h after exposure 98. This exposure was accompanied by increases in bronchoconstrictive lipid mediators (thromboxane B2, prostaglandin F2 α, and leukotrienes) immediately after exposure, and delayed influx of neutrophils (24 h) 98, 99. These temporal relationships suggest that neutrophil infiltration may be a sufficient but not a necessary condition for the onset of bronchial hyperreactivity and that injury to cells normally present in the lung, e.g.…”
Section: Responsementioning
confidence: 95%
“…Airborne aldehydes have been implicated as contributing factors to the increase in asthma and allergic disease in world urban populations (Leikauf,; McGwin et al,; Arif and Delclos,). In animal models, acrolein induces airway hyper‐responsiveness (Myou et al,), production of leukotrienes (Leikauf et al,), increased mucous production (Borchers et al,), and airway hypersensitivity (Roux et al,), all hallmarks of asthma. Thus, as one of the more common components of anthropogenic pollution, acrolein poses a potential health risk for the development of asthma in exposed populations.…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoke extract contains many toxic substances, in addition to nicotine, that may contribute to impaired vascular reactivity. Acrolein and acetaldehyde are highly soluble components of cigarette smoke extract and have been shown to cause irritation of airway and ocular mucosa in humans, impair mucociliary clearance in the upper airway, produce pulmonary edema in animals, and damage epithelial cells (13,14,30,45). In addition, Holden et al (20) have shown that cigarette smoke extract increases albumin flux across cultured porcine pulmonary endothelium, and this effect was predominantly due to the vapor phase of cigarette smoke.…”
mentioning
confidence: 99%